LANGSTON HUGHES’S STYLE IN HIS STORY «ON THE ROAD» - FEDORIAKA, Ludmyla; REVENKO, Viktoria (Науковий вісник Ужгородського університету. Серія Філологія, 2020)
Langston Hughes (1902‒1967) is considered to be paradoxically one of the most ambiguous as well as under- standable writers of the American «Harlem Renaissance». His short stories as a key genre of his literary paradigm brought him a world fame and he is remembered now thanks to the peculiar author’s manner of writing. In this article the investigators deal with the problem of L. Hughes’s individual style, – a criterion, which, indeed, made this literary man a wide popularity among his famous contemporaries and future generations of writers. This constituent part of his creative work deserves a separate deep and detailed analysis. The authors of this article make an attempt to trace the uniqueness of L. Hughes’s style on the example of his well-known fragment «On the Road». As a result of the scientific work it was proved that the author widely used all stylistic levels – phonetics, lexicology, syntax and semasiology. On the level of phonostylistics the author of the story widely uses alliteration, onomatopoeia, graphon and italicized words which are helpful to demonstrate natural phenomena and to portray the main hero. From the viewpoint of lexicology, L. Hughes’s story is specific because the author prefers words of neutral and colloquial origin as he wants both to illustrate characterological features of Sargeant and to show the key addressee of the story. Here, we deal with the fact that L. Hughes wrote his fiction about ordinary people to be read by them, so, the choice of his word-stock is logical. Syntactically, the story «On the Road» is very representative as is considered to be suitable for realization the author’s goal. L. Hughes uses many stylistic figures in this piece of prose. Elliptical and nominal sentences, detached and parallel constructions, inversion, anaphoric sentences, repetitions, enumerations serve to reveal the main hero’s physical and psychological state. Means and devices depicting the imaginary background of the story are also presented in the text by the author. In this regard, L. Hughes uses epithets, similes, but they are frequently used in the laconic text of the story and create the image of winter and the destiny of the main hero. So, having explored stylistic peculiarities of the story «On the Road», the authors of this article came to conclusion that the author uses language media of all linguistic levels, he obtains the capaсity to combine them in a comparatively short textual space, and this combinability leads to the birth of a particular, extra-ordinary style of the author. One should take into account that this non-traditional manner of Hughes’s expressing thoughts also testifies about the fact that the usage of such style of writing is very powerful and appropriate to realize his global aim – to raise the racial problem, which was spread in America in the 30s, and which, moreover, L. Hughes was personally survived and, therefore, cordially sympathized himself. That’s why, in this story L. Hughes declares himself not only as a brilliant linguist but and as a convinced fighter against racism in the USA also with the help of his unique style of writing.